FACTORS AFFECTING THE PERFORMANCE OF SHARIA BANK EMPLOYEES - Yolanda Adista Septiani Aksa; Rudi Aryanto; Mail Hilian Batin (Indonesian Journal of Multidisciplinary Sciences (IJoMS), 2023)
This research is based on the background that employee performance is the main thing that companies must pay attention to when carrying out their work activities. For this reason, this problem requires company management to plan to increase competency, distribute knowledge (knowledge sharing) and carry out work supervision more strictly in order to improve the performance of its employees. This research aims to test the variables of Competency, Knowledge Sharing and Work Supervision on Employee Performance at Bank Sumsel Babel Syariah KC Palembang. This research uses quantitative methods. The population in this study was 62 employees using a purposive sampling technique. The sample in this study consisted of 33 respondents who were employees of Bank Sumsel Babel Syariah KC Palembang. Primary data was obtained from distributing questionnaires to employees and analyzed using the validity test method, reliability test, while data analysis techniques used the classic assumption test, multiple linear regression analysis, t test, f test and r test. The research results show that the competency variable has a positive and significant effect on employee performance at Bank Sumsel Babel Syariah KC Palembang. The results obtained were tcount > t table (2.438 > 1.699) with a significance of 0.021 < 0.05. The knowledge sharing variable has a positive and significant effect on employee performance at Bank Sumsel Babel Syariah KC Palembang. The results obtained are t count > ttable (2.160 > 1.699) with a significance of 0.039 < 0.05. The work supervision variable has a positive and significant effect on employee performance at Bank Sumsel Babel Syariah KC Palembang. The results obtained are tcount > ttable (2.253 > 1.699) with a significance of 0.032 < 0.05. Simultaneously, the three variables have a positive and significant effect on employee performance at Bank Sumsel Babel Syariah KC Palembang. The results obtained are Fcount 12.925 > Ftable 2.93 and a significance of 0.000 < 0.05.